A Rare Case of Filariasis Presenting as An Abscess - Bhartiya, Richa; Kumari, Nawanita; Agrawal, Pallavi; Rajnish, Kumar (Annals of Pathology and Laboratory Medicine, 2018)
Filariasis is a major public health problem in tropical countries including India. Filariasis is transmitted by the bite of culex mosquitoes. The diagnosis is conventionally made by demonstrating microfilaria in the peripheral blood smear. Microfilaria has been incidentally detected in FNAC smears from various sites. However, the presence of filarial worm in breast aspirate is unusual. We report a case of lactating female with breast lump presenting as tender subcutaneous nodule, clinically mimicking as a breast abscess, which on aspiration cytology revealed presence of numerous microfilaria in the background of inflammatory cells.